Islamic liberation psychology : the transformational force of self-development, community empowerment, and revolutionary change - Mohr, Sarah Huxtable (New York : Routledge, 2024)
"Islamic Liberation Psychology is a thoughtful and groundbreaking guide to liberatory and decolonial thought. The book has a wide range of uses, from individuals seeking self-development, to community organizers, to change makers generally. Chapters explore liberation psychology from an Islamic perspective and use autoethnography to frame the theory and make it more relevant and applicable. This book makes a substantial contribution to a greater understanding of a variety of topics including anti-racism, feminism, utopianism, community development, arts and creativity, and other topics central to Islamic liberation psychology"--
Foreword / by Farid Esack -- Preface -- Introduction -- 1. The Theoretical Basis: De-ideologizing Reality -- 2. The Theoretical Goal: Utilizing the Virtues of the People -- 3. Self-development -- 4. Community Empowerment -- 5. Revolutionary Change -- Conclusion: Historical Memory and Utopian Vision -- Index.
Keywords: Social psychology; Liberty -- Religious aspects -- Islam; Social change -- Religious aspects -- Islam; PSYCHOLOGY / Social Psychology